ENHANCING STUDENTS’ VOCABULARY MASTERY USING CARTOON MOVIE AT THE EIGHTH GRADE CLASS OF SMP NEGERI 3 DUHIADAA - Arbie, Nur Melisa (Journal of Education and Teaching Learning, 2024)
This research aimed to improve the vocabulary mastery of eighth-grade students at SMP Negeri 3 Duhiadaa using cartoon films that focus on verbs and nouns. Researchers used one group of pre-experimental research where data was obtained from the pre-test and post-test. The population of this study was the eighth grade (VIIIB) of SMP Negeri 3 Duhiadaa. The research sample was taken using a purposive sampling technique; there were 23 students. The findings of this research showed that the differences between students before and after using cartoon films are significantly different. The students' pre-test average score in total vocabulary was 42.8 to 79.3, with a presentation of an increase of 85.3%. The results of data collection were calculated using SPSS. Wilcoxon signed test analysis showed that Sig. (2-tailed) = 0.00, which is smaller than α = 0.05. It means there is a significant difference in students' vocabulary before and after using cartoon films. Based on these findings, it can be concluded that cartoon films effectively increase the vocabulary of eighth-grade (VIII B) students at SMP Negeri 3 Duhiadaa.